Intravital imaging of eosinophils: Unwrapping the enigma. Issue 1 (14th March 2020) - Nguyen, William N T; Jacobsen, Elizabeth A; Finney, Constance A M; Colarusso, Pina; Patel, Kamala D
Abstract: Eosinophils are traditionally associated with allergic and parasitic inflammation. More recently, eosinophils have also been shown to have roles in diverse processes including development, intestinal health, thymic selection, and B-cell survival with the majority of these insights being derived from murine models and in vitro assays. Despite this, tools to measure the dynamic activity of eosinophils in situ have been lacking. Intravital microscopy is a powerful tool that enables direct visualization of leukocytes and their dynamic behavior in real-time in a wide range of processes in both health and disease. Until recently eosinophil researchers have not been able to take full advantage of this technology due to a lack of tools such as genetically encoded reporter mice. This mini-review examines the history of intravital microscopy with a focus on eosinophils. The development and use of eosinophil-specific Cre (EoCre) mice to create GFP and tdTomato fluorescent reporter animals is also described. Genetically encoded eosinophil reporter mice combined with intravital microscopy provide a powerful tool to add to the toolbox of technologies that will help us unravel the mysteries still surrounding this cell. Graphical Abstract: Genetically encoded eosinophil reporter mice combined with intravital microscopy provide a powerful tool to help answer questions about eosinophil behavior in health and disease.